2009
DOI: 10.1507/endocrj.k08e-177
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor DAX1 in Human Prostate Cancer: A Novel Independent Biological Modulator

Abstract: Abstract. The orphan nuclear receptor DAX1 (dosage-sensitive sex reversal-AHC critical region on the X chromosome gene 1; NR0B1) has been known for its various roles in human development, specifically sex determination and steroidogenesis. Its expression has been reported in endocrine and sex steroid-dependent neoplasms such as human adrenocortical, pituitary, endometrial, and ovarian tumors. Prostate cancer is also sex steroid-dependent tumor in which androgens play important roles in the pathogenesis and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
1
20
1
Order By: Relevance
“…26,28 Whereas, the subcellular localization of NR0B1 was various among cases with the present lung adenocarcinoma. Kawajiri et al 43 reported that NR0B1 localization changed during pituitary development from nucleocytoplasmic at embryonic day 10.5 to nucleus at day 18.5.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…26,28 Whereas, the subcellular localization of NR0B1 was various among cases with the present lung adenocarcinoma. Kawajiri et al 43 reported that NR0B1 localization changed during pituitary development from nucleocytoplasmic at embryonic day 10.5 to nucleus at day 18.5.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, the knocked-down expression of NR0B1 did not affect the cell proliferation of A549 cells. This might be attributable to the difference of cell types; Saito et al 26 and Nakamura et al 28 did not find any correlation of NR0B1 expression level with the Ki-67 labeling index, a well-established marker for cell proliferative activity, in the endometrial adenocarcinoma of uterus and prostate. The present study on the clinical cases of lung adenocarcinoma showed that NR0B1 expression level did not correlate with the size of tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is reported to be high in normal prostate epithelial cells but reduced in BPH (Holter et al 2002, Agoulnik et al 2003. Nuclear expression of DAX1 is also reported to be reduced with increasing Gleason grade (Nakamura et al 2009a). However, in the same report, normal tissue had no detectable DAX1 expression.…”
Section: Dosage-sensitive Sex Reversal (Dss/dax1 or Nr0b1)mentioning
confidence: 83%
“…DAX-1 immunoreactivity correlated inversely with Gleason score, a grading system used to assess malignancy in this type of cancer [153].…”
Section: Prostatementioning
confidence: 93%